Joint routing and scheduling for electric vehicles in smart grids with V2G - Triviño-Cabrera, Alicia; Aguado-Sánchez, José Antonio; De-la-Torre-Fazio, Sebastián Bienvenido (Elsevier, 2019)
Modern distribution systems with high penetration of Electric Vehicles (EVs) are the focus of increasing attention. EVs charging strategies impact on power networks operation and they can even affect driving patterns when considering Vehicle-to-Grid (V2G) market-driven scenarios. This paper proposes a joint EV routing and charging/discharging scheduling strategy to operate an EV fleet. Particularly, we propose a mathematical framework based on a mixed-integer linear programming problem with the goal of maximizing the revenue of EV users. This approach is illustrated and tested using the IEEE 37-node test feeder. The results show that slight changes in driving patterns can provide benefits to EV users and improve the network operation. The correct design of the price dynamics is concluded to be key for promoting V2G participation.
Keywords: Vehículos eléctricos; Routing; Scheduling; Bidirectional; V2G; Electric vehicle; Charge; Discharge